Single–gene knockout of RNLS or HIVEP2 are insufficient to protect β–cell spheroids from allo– and xeno–rejection - Karaoglu, Ismail Can; Odabas, Arda; Önder, Tamer; Kizilel, Seda (Frontiers in Immunology, 2026)
Introductionβ-Cell replacement therapy offers a potential cure for type 1 diabetes, but its success is limited by rapid graft rejection. While genome-wide CRISPR screens have recently identified RNLS and HIVEP2 as candidate genes capable of protecting β-cells from autoimmune destruction, their efficacy against the distinct mechanisms of allogeneic and xenogeneic rejection remains unknown. This study aimed to test the hypothesis that single-gene ablation of RNLS or HIVEP2 protects β-cell spheroids from allo- and xenorejection in immunocompetent hosts.MethodsMurine β-TC-6 and human EndoC-βH1 β-cell lines were genetically edited using CRISPR-Cas9 to knockout RNLS or HIVEP2. Editing efficiencies were confirmed via T7 endonuclease I assay and Tracking of Indels by Decomposition (TIDE) analysis. Cells were aggregated into uniform, size-controlled spheroids using an optimized agarose suspension culture. Functional integrity was assessed via glucose-stimulated insulin secretion (GSIS). To evaluate immune evasion in vivo, luciferase-labeled spheroids were transplanted subcutaneously into immunocompetent CD-1 mice, modelling allogeneic (murine-to-murine) and xenogeneic (human-to-murine) rejection, with graft survival monitored longitudinally by bioluminescence imaging.ResultsRobust editing efficiencies were achieved for both targets. Functional characterization indicated that Rnls deletion modestly impaired GSIS in murine cells, whereas HIVEP2 deletion showed no functional alterations in either cell line. In vivo assessment revealed no protective effects of RNLS or HIVEP2 deletion; grafts from both knockout groups displayed rejection kinetics indistinguishable from non-targeting controls. While allogeneic grafts survived longer than xenogeneic grafts, both were ultimately cleared by the host immune system regardless of genotype.DiscussionThese data indicate that single-gene deletions of RNLS or HIVEP2 are insufficient to protect β-cell grafts from the barriers of allo- or xenorejection. By defining the limitations of these targets in isolation, our findings highlight the necessity for combinatorial genome editing strategies or complementary integration with immunomodulatory biomaterials to achieve effective and sustained β-cell graft survival.